Centrifugal telencephalic afferent connections to the main and accessory olfactory bulbs - MohedanoMoriano, Alicia; de la Rosa-Prieto, Carlos; Saiz-Sanchez, Daniel; Ubeda-Banon, Isabel; Pro-Sistiaga, Palma; de Moya-Pinilla, Miguel; Martinez-Marcos, Alino (Frontiers in Neuroanatomy, 2012)
Parallel to the olfactory system, most mammals possess an accessory olfactory or vomeronasal system. The olfactory and vomeronasal epithelia project to the main and accessory olfactory bulbs, which in turn project to adjacent areas of the telencephalon, respectively. New data indicate that projections arising from the main and accessory olfactory bulbs partially converge in the rostral telencephalon and are non-overlapping at caudal telencephalic levels. Therefore, the basal telencephalon should be reclassified in olfactory, vomeronasal, and mixed areas. On the other hand, it has been demonstrated that virtually all olfactory- and vomeronasal-recipient structures send reciprocal projections to the main and accessory olfactory bulbs, respectively. Further, non-chemosensory recipient structures also projects centrifugally to the olfactory bulbs. These feed-back projections appear to be essential modulating processing of chemosensory information. The present work aims at characterizing centrifugal projections to the main and accessory olfactory bulbs arising from olfactory, vomeronasal, mixed, and non-chemosensory recipient telencephalic areas. This issue has been addressed by using tracer injections in the rat and mouse brain. Tracer injections were delivered into the main and accessory olfactory bulbs as well as in olfactory, vomeronasal, mixed, and non-chemosensory recipient telencephalic structures. The results confirm that olfactory- and vomeronasal-recipient structures project to the main and accessory olfactory bulbs, respectively. Interestingly, olfactory (e.g., piriform cortex), vomeronasal (e.g., posteromedial cortical amygdala), mixed (e.g., the anterior medial amygdaloid nucleus), and non-chemosensory-recipient (e.g., the nucleus of the diagonal band) structures project to the main and to the accessory olfactory bulbs thus providing the possibility of simultaneous modulation and interaction of both systems at different stages of chemosensory processing.